Effect of pulsed electric field on diabetes-induced glycated enzyme, oxidative stress, and inflammatory markers in vitro and in vivo. (6th October 2021) - Rezaeinezhad, A; Eslami, P; Afrasiabpour, Gh; Mirmiranpour, H; Ghomi, H
Abstract: This study focused on the effect of pulsed electric field (PEF) on the modification of superoxide dismutase (SOD) to recover its activity ( in vitro ) and thereby reverse oxidative stress in diabetic mice ( in vivo ). The result of the in vitro assay demonstrated that PEF could modify the glycated SOD structure through a change in the electrostatic environment of the protein. This modification leads to an 83% and 31% increase in the enzymatic activity of in vitro and in vivo assays, respectively. The in vivo assessment results show a decrease in oxidative stress biomarker indices, advanced glycation end products content, and inflammatory cytokines concentrations. However, the change in blood glucose level is not significant. According to the results, PEF would be effective in diabetes therapy and could be employed as a complementary method.